QoS Design Consideration for Enterprise and Provider’s Network at Ingress and Egress Router for VoIP protocols - Manjur Kolhar; Mosleh M Abualhaj; Faiza Rizwan (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Compliance with the Service Level Agreement (SLA) metric is a major challenge in a Multiprotocol Label Switching Virtual Private Network (MPLS VPN) because mandatory models must be maintained on both sides of the MPLS VPN in order to achieve end-to-end service levels. The end-to-end service of an MPLS VPN can be degraded owing to various issues such as distributed denial of service (DDoS), and Random Early Detection (RED) that prevents congestion and differentiates between legitimate and illegitimate user traffic. In this study, we propose a centralized solution that uses a SLA Violation Detector (SLAVD) and intrusion detection to prevent SLA violation.